125I Seed Brachytherapy for Refractory Loco-Regional Recurrence of Non-Anaplastic Thyroid Cancer - Yu, Huimin; Zhang, Hongtao; Gao, Zhen; Liu, Xiaoli; Zhang, Lijuan; Di, Xuemin; Wang, Zeyang; Liu, Zezhou; Sui, Aixia; Wang, Juan; Shi, Gaofeng (Frontiers in Oncology, 2022)
Purpose: The purpose of this research was to evaluate the feasibility and efficacy of 125I seed brachytherapy as salvage treatment for recurrence from non-anaplastic thyroid cancer refractory to other modalities. Methods: Between June 2006 and September 2019, fifteen patients with recurrent non-anaplastic thyroid cancer were treated with 125I seed brachytherapy. 125I seeds were implanted into the tumor under the guidance of CT and/or ultrasound images with the median prescription dose of 120 Gy (range 100-140 Gy). The median seed number was 80 (range 10-214). Clinical efficacy was evaluated with Response Evaluation Criteria in Solid Tumors. Findings: Fifteen patients were selected, eleven of whom had papillary carcinoma, two suffered from follicular carcinoma, and two were diagnosed with medullary carcinoma. These patients had twenty-four nodes in total. After they received salvage surgery and/or radioactive iodine (RAI) therapy, local recurrence was detected in all of them. No less than one node was observed in everyone’s cervical or supraclavicular areas, and four patients had lung metastatic. The median follow-up period lasted 48 months (range 5-93 months). All patients did not develop locoregional recurrence after experiencing 125I seed brachytherapy. Only three of them formed new metastases in nontarget regional nodes after brachytherapy, and additional brachytherapy can solve all regional failure problems. No significant adverse events were observed in any patient. Implications: For the chosen patients, 125I seed brachytherapy is feasible for treating refractory local recurrence from non-anaplastic thyroid cancer. Further studies are required to determine the role of 125I seed brachytherapy in the treatment of thyroid cancer.